Draft Annual Plan 1988-89 Volume-II Statistical Data Government of Andhra Pradesh - Planning Commission (Planning Commission, 1988)
Draft Annual Plan - 1988-89 Head Or Development - Outlay And Expenditure, The Amount Of Rs.820.00 Lakhs Required Under Tills Head Is Met By Meeting The Expenditure Ultimately From The Provisions Earmarked For Major Projects
Finance and Planning (Planning Wing) Department
Finance and Planning (Planning Wing) Department Government of Andhra Pradesh